THE IMPLEMENTATION OF GENRE BASED APPROACH ON SPEAKING SESSION OF EIGHTH GRADE OF THE STUDENTS AT SMPN 03 GONDANGREJO KARANGANYAR : AN ETHNOGRAPHYSTUDY - FITRIANA, LINDA (2011)
This research aims at describing the implementation of Genre-Based Approach in speaking session. It is conducted to describe the objective of learning, the material, the syllabus, the teacher roles, the student roles, classroom procedure, lesson plan, problem faced by the teacher and the teachers' way to solve the problems. The research paper is an ethnographic research in which the data are in the form of field note, interview script, and video recording. The writer gets the data from event, informant and document. The techniques of collecting data are observation, interview and documentation. The result of the research shows that the implementation of Genre-Based Approach in speaking session used by the teacher at SMPN 03 Gondangrejo, Karanganyar is appropriate with the principles of genre. The classroom procedure in speaking session consist of four stages. The stages are: BKOF, MOT, JCOT, ICOT. The teacher uses handbook and workbook as material sources. The teacher roles are: teacher as classroom manager, facilitator and instructor. The students roles are: students as listener and performer. The research also shows the problems faced by the teacher, namely the students' limited vocabulary, the students' poor grammar mastery and the students' poor of pronunciation. For the first problem, the teacher asks the students to consult dictionary when the students meet difficult words. While for the second problem, the teacher provides opportunity for the students to ask about material then teacher explains the material until the students understood. For the third problem, the teacher gives correct pronunciation of words then the students should repeat it, the teacher also gives correction if the students get in wrong pronunciation.